HUBUNGAN FUNGSI KOGNITIF TERHADAP KESEIMBANGAN PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA (PSTW) BUDI MULIA 3 JAKARTA - Mohammad Ali; Erna Sariana; Deiza Novamaria Aziza (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Cognitive is a combination of processes in the brain that includes the ability to learn, remember, and make a large impact on the health and overall well-being of individuals. Balance is the result of complex integration and coordination of several systems consisting of sensory/perception, cognitive influences (such as attention, motivation, and intention), and motor processes. The purpose of this study was to determine the relationship between cognitive function and balance in the elderly at the Tresna Werdha Budi Mulia 3 Social Home in Jakarta. Using a cross-sectional method with a sample of 109 respondents selected by purposive sampling technique. Cognitive function parameters using the mini-mental state examination and balance parameters using the timed up and go test. Statistical analysis using Spearman-Rank Correlation obtained p-value = 0.205 (p > 0.05) and r value of -0.122 which means that the correlation is very weak between cognitive function and balance, with a negative direction. There is no significant relationship between cognitive function and balance in the elderly at the Tresna Werdha Budi Mulia 3 Social Institution, Jakarta.